Constructs of "Development" among CDC faculty and in students student research studies - Cagasan, Editha G. (The Philippine Journal of Development Communication, 2008)
The plurality of realities influencing the constructs of development among development communicators prompted the conduct of this research project. Content analysis, meta-research, and discourse analysis were used to answer the question: What are the constructs of development that have emerged among the students and faculty of the College of Development Communication (CDC) from 1972 to 2004? Ninety-nine graduate and 93 undergraduate research manuscripts and the transcripts of the focus group discussion (FGD) participated in by selected CDC faculty were analyzed.